"Because of incest which one of the two of them committed": A Letter about Two Third Crusade Participants from the Archivo Catedralicio de Toledo. (31st December 2021) - Lincoln, Kyle C.
Abstract: A letter preserved in the cathedral archives of Toledo describes the case of two poor and penitent crusaders, who had been sent to Castile to crusade in the 1190s. Although very little is known about the two men, this study attempts to contextualize their crusading activity within contemporary events in order to provide an additional, if minor, point of detail that can enrich the larger narrative of crusading in the period. In doing so, it also demonstrates the close ties between Rome, Iberia, and the crusading world in the second half of the twelfth century, as well as offering a specific and poignant example of penitential crusading in the same era.